A Multicenter, Prospective, Randomized, Contralateral Study of Tissue Liquefaction Liposuction vs Suction-Assisted Liposuction. (23rd January 2018) - Hunstad, Joseph P; Godek, Christopher P; Van Natta, Bruce W; Kortesis, Bill G; Bharti, Gaurav; Crantford, John C; Daniels, Mark A; Andrew, Mark S
Abstract: Background: Tissue liquefaction liposuction (TLL) deploys a novel energy source utilizing a stream of warmed, low-pressurized, and pulsed saline to extract fat tissue. Objectives: Compare TLL to suction-assisted liposuction (SAL) to determine which device is more efficient for surgeons and provides better recovery for patients. Methods: Thirty-one adult female patients were followed prospectively in a contralateral study design comparing differences in bruising, swelling, tenderness, and incision appearance ratings between TLL and SAL procedures. Surgical efficiency and appearance of the lipoaspirate were also compared. Results: All 31 patients successfully completed the study. For TLL and SAL procedures, the average volumes of infusion (1.242 vs 1.276 L) and aspirated supernatant fat (704 vs 649 mL) were statistically similar. TLL median fat extraction rate was faster than SAL (35.6 vs 25 mL/min; P < 0.0001), and stroke rate was reduced in TLL vs SAL procedures (48 vs 120 strokes/min; P < 0.0001), and both were statistically significant. The mean total scores for bruising, swelling, treatment site tenderness, and incision appearance were lower, indicating improved patient recovery on the TLL side. Conclusions: TLL and SAL techniques produced comparable volume of fat aspirate. TLL demonstrated a 42% faster fat extraction rate and a 68% reduction in arm movements needed to complete the procedure compared to SAL, both of these differences are statistically significant. The TLL side was noted to have reduced bruising and swelling and improved incision site appearance with less tenderness compared to the SAL side. Level of Evidence: 2: